THE ART OF LANGUAGE EMPHASIS (TAWKĪD) AND ITS BENEFITS IN THE HADITHS WITHIN RIYĀḌ AL-ṢĀLIḤĪN - Mufidah, Azimatul; Faisah, Nurul (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
This research discusses the art of language emphasis (Tawkīd) and its benefits in the Hadiths of the Prophet Muhammad (PBUH) found in the book Riyāḍ al-Ṣāliḥīn. The study of the rhetoric of Hadiths is not a new phenomenon, but its quantity remains limited. Moreover, the existing studies primarily focus on the science of bayān ma’ani (exposition of meanings) and only touch upon the science of badī' (eloquence and rhetorical figures). There is still a dearth of research on the stylistic aspects of language in the science of ma’āni (semantic sciences), as explored in this study. Therefore, this research aims to fill the gap, overcome stagnation, and address the scarcity of references in the study of Hadith rhetoric. The research employs a literature review methodology, collecting data from various books, texts, and relevant journals. This article discusses the benefits underlying the art of language used by the Prophet Muhammad (PBUH). The findings reveal that 16% of the Hadiths in Riyāḍ al-Ṣāliḥīn employ the technique of Tawkīd. Out of the six types of emphasis, only five were found in examples within this book. These five styles of emphasis are utilized for 13 different purposes. Additionally, several examples of responses to denial or doubt without the use of emphasis (Tawkīd) were also identified.[Penelitian ini membahas tentang seni bahasa taukīd/penegasan dan faidahnya pada hadis-hadis Rasulullah SAW di dalam kitab Riyāḍ al-Ṣālihīn. Kajian tentang balāgah hadis bukan hal yang baru, tapi jumlahnya masih sedikit. Di samping itu, kajian tentangnya masih berkutat pada topik ilmu bayān ma’ani dan sedikit dari ilmu badī’. Kajian gaya bahasa dalam ilmu ma’āni seperti penelitian ini, masih kurang. Oleh karena itu, Penelitian ini bertujuan mengisi kekosongan, stagnasi, dan kelangkaan referensi kajian balāgah hadis. Penelitian ini menggunakan metode studi pustaka dengan teknik mengumpulkan data/memanfaatkan sumber dari beberapa buku, kitab, jurnal yang sesuai dengan pembahasan. Artikel ini membahas faidah di balik seni bahasa Rasulullah SAW. Hasilnya, diketahui bahwa 16% hadis dalam kitab Riyāḍ al-Ṣāliḥin menggunakan ṣigat taukīd. Dari enam jenis taukīd, hanya lima yang dapat penulis temukan contohnya dalam kitab ini. Kelima Gaya penegasan tersebut digunakan untuk 13 macam faidah. Di sini, juga didapati beberapa contoh respon terhadap pengingkaran/keraguan, tanpa menggunakan penegasan/taukīd.]